IMPLEMENTATION OF PENAL MEDIATION IN CRIMINAL LAW - Aji Sudarmaji; Sri Endah Wahyuningsih (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Penal mediation is an alternative settlement of criminal cases emphasizing restorative justice approach, which is carried out between the victims and the offenders or his/her families with the purpose of restoring the balance in the society. The major problem in this research is, firstly, how is the penal mediation in criminal law enforcement implemented today? Secondly, how are the weaknesses of the implementation of the penal mediation in criminal law enforcement today? Thirdly, how is the penal mediation in criminal law enforcement based on Pancasila values of justice constructed today? In order to answer the problems mentioned above is obtained by using social legal research method, conducted with case studies that have already been through the legal processes by law enforcement officials until the court makes the decision, this kind of legal processes is deemed to have injured sense of justice in the community by the society. Penal mediation provides the best way to resolve problems or conflicts between the perpetrator and the victims by engaging between them directly in order to solve the problems with peaceful means in accordance with Pancasila values of justice.  The conclusion in this study is the current formulation of the regulations has not accommodated penal mediation as a form of settling disputes outside the criminal justice processes. Penal mediation arrangements in the future must be included in the substantive criminal law, the formal criminal law and the implementation of criminal law.  Keywords: Construction, Penal Mediation, Pancasila Justice.